2013
DOI: 10.1182/blood-2013-04-497354
|View full text |Cite
|
Sign up to set email alerts
|

Robust ZFN-mediated genome editing in adult hemophilic mice

Abstract: Key Points AAV delivery of ZFNs and corrective Donor vectors to adult mouse liver results in stable human factor IX levels, normalizing hemophilic clotting times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 12 publications
(14 reference statements)
5
122
0
1
Order By: Relevance
“…67 The study was performed in young mice, in which the hepatocytes are still proliferating and HDRmediated mechanisms are still active. Importantly, the strategy has also worked in adult hepatocytes that have exited the cell cycle, through a combination of HDR-and NHEJ-mediated repair mechanisms, 75 extending the applicability of the approach. By following similar strategies, CRISPRCas9 was successfully used to treat a mouse model of hereditary tyrosinemia caused by fumarylacetoacetate hydrolase (FAH)-deficiency.…”
Section: Preclinical Studies Testing Hepatocyte Genome Editing Stratementioning
confidence: 99%
See 1 more Smart Citation
“…67 The study was performed in young mice, in which the hepatocytes are still proliferating and HDRmediated mechanisms are still active. Importantly, the strategy has also worked in adult hepatocytes that have exited the cell cycle, through a combination of HDR-and NHEJ-mediated repair mechanisms, 75 extending the applicability of the approach. By following similar strategies, CRISPRCas9 was successfully used to treat a mouse model of hereditary tyrosinemia caused by fumarylacetoacetate hydrolase (FAH)-deficiency.…”
Section: Preclinical Studies Testing Hepatocyte Genome Editing Stratementioning
confidence: 99%
“…65,74,79 NHEJ is active throughout all the phases of the cell cycle and works well in hepatocytes. 80,81 While HDR works preferentially in dividing cells, during the S/G2 phase, it has also been shown that it can act in adult hepatocytes, 75,77 which are mainly arrested in the G1 phase. HDR efficiency is influenced by the type of gene editing to be performed: thus, small deletion or mutations are much easier to achieve than large gene insertions.…”
Section: Key Pointmentioning
confidence: 99%
“…42,43 Zinc finger technology delivered via AAVs has been used to target the liver in a hemophilia model. 44 Proof-of-concept studies have also demonstrated that CRISPR/Cas9 technology can be used to target the liver to treat a genetic disease. 45 With all of the new technologies available to address AAT gene therapy, the future prospects for licensed gene therapy products for this disease seem very bright.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition to enabling the introduction of gene modification that can enhance autologous cell therapies, targeted nucleases can also be combined with viral vectors-including AAV-to mediate genome editing in situ ). For instance, delivery of an AAV vector encoding a ZFN pair designed to target a defective copy of the factor IX gene, along with its repair template, led to efficient gene correction in mouse liver, increasing factor IX protein production in both neonatal ) and adult (Anguela et al 2013) models of the disease. In vivo genome editing also recently enabled the restoration of dystrophin gene expression and the rescue of muscle function in mouse models of Duchenne muscular dystrophy (Long et al 2015;Nelson et al 2015;Tabebordbar et al 2015).…”
Section: Therapeutic Genome Editingmentioning
confidence: 99%